Reform of Collective Bargaining in Spain and Industrial Relations System - Casas Baamonde, Maria Emilia (Cuadernos de Relaciones Laborales, 2014)
The article discusses the recent reforms of the collective bargaining’s legal framework of general efficiency, collective bargaining representative of the Spanish legal system, introduced in the years 2010 to 2014, coinciding with the global economic and financial crisis, which began in 2008, the European political and monetary crisis and the and political-economic crisis en Spain. The reforms, and especially the recent legal reforms of 2012-2014, have had a qualitative impact on the bargaining system, shifting the regulation’s orientation from the constitutional right to collective bargaining, and to the binding force of conventions, closely connected with the freedom of association, to the constitutional right to free enterprise and constitutional duty of the authorities to ensure the safeguarding of productivity. The legislative reforms of 2012 aimed at ensuring that collective bargaining is a tool, not an obstacle, to adapt working conditions to the specific circumstances of the company. For it they have postponed the traditional role of the collective agreement to compensate the fundamental inequality of labor relations by limiting individual autonomy and the power of corporate decision, as well as emphasizing the management function of the collective agreement through different techniques with convergent results: applicative priority of the company’s collective agreement as a mandatory rule for higher-level collective bargaining, modification and unique company inapplicability of the collective agreement through binding arbitration public, ante tempus modification of the collective agreement, and the temporal limitation of the ultraactive effectiveness of collective agreements within agreement renewal processes. To achieve its reformation goals, and yet there is some exception in a non-minor matter (ultra-activity of collective agreements) in which reformation goals are achieved through the transfert of competencies by the law to the collective bargaining, labor law flexibilization tends to self-sufficiency and rigidness. These reforms project their effects on labor relations system as a whole, drawing lines of transformation of undeniable legal significance, among which stands the promotion, using imperative techniques, of collective bargaining at company level, which, beyond their impact on the structure of collective bargaining, is offered as a guarantee of the higher flexibility and corporate competitiveness, affects the functions of the right to collective bargaining channeled a principle of differentiation that old attempts to individualize working conditions failed, and displaces the powers of trade unions and business confederations to representations of companies and businessmen.
Keywords: collective bargaining; legislative reforms; constitution; free enterprise; flexibility; trade unions; public binding arbitration; ultraactive effectiveness